Land use monitoring on the example of the Iglinsky district - Ilnur R. Miftakhov, Nataliia A. Zotova, Marat G. Ishbulatov,; Gulfiya R. Karimova, Khalida G. Aktuganova, (Opción, 2019)
The study aims to investigate the land use monitoring on the example of the Iglinsky district of the Republic of Bashkortostan via the analytical proсеssing aimed to study and to generalize the deciphering materials, field surveys, statistical reports in order to provide valid data. As a result, land monitoring is necessary for the development and determination of cost of rational agrotechnical actions for restoration of fertility and primary cultivation of lands and their effective use. In conclusion, one of the reasons for land deterioration is the unsystematic economic activity of most agro-industrial enterprises.